Learning Embedded Systems with Multi-Microcontroller Evaluation Tool - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2011)
Embedded systems have an everyday presence and direct impact in every day’s lives. Therefore, learning institutions are continuously improving their courses in microcontroller and embedded system programming. Although the diversity of curriculums, the availability of learning tools, where the student can practice and improve their skills, is a key factor to the success of the learning process. The platform developed and presented in this paper results from author’s experience in teaching embedded systems. From the analysis of teaching/learning needs, a learning environment based on the Freescale HC11, MCS51, and Microchip PIC 16 Series families was designed. This tool can be expanded by modules and adjusted, at a specific time, to student's real needs. All modules can be interconnected by an IDE bus, allowing expanding the capabilities of the platform. The developed modules allow the practice of subjects related with digital IO, analogue interface, user interface, wireless communications, and energy management and conservation. Keywords - Embedded system, learning, laboratory, programming, microcontroller.